Phosphate fertilization and bioactivator influences on fractions of organic matter and soil microbial biomass (Research, Society and Development, 2022)
Soil organic matter is considered a potential source of phosphorus (P) for plants because of biological cycling. Bioactivators are characterized as tools that can help soil microbial activity and the availability of P demanded by plants. The objective of this study was to evaluate the influence of the use of bioactivators and phosphate fertilization on the activity of soil microbial biomass and humified fractions of organic matter. The experimental design was completely randomized in a factorial scheme (6 × 2), with the first factor consisting of six doses of phosphorus applied to the soil (0, 30, 60, 90, 120, and 150 kg ha-1 of P2O5), using triple superphosphate as the source, and the second factor being the presence or absence of soil and plant bioactivator application, with four replications. The evaluated characteristics were soil microbial biomass carbon (SMBC), soil basal respiration (SBR), microbial biomass nitrogen (MBN), metabolic quotient (qCO2), microbial quotient (qmic), total organic carbon (TOC), fulvic acid fraction carbon (FAC), humic acid fraction carbon (HAC), and humin fraction carbon (HUMC). The use of soil and plant bioactivators and mineral phosphate fertilizer promoted changes in soil microbial activity. Increasing doses of phosphate fertilization promoted a reduction in the carbon characteristics of microbial biomass and basal soil respiration in the presence or absence of soil and plant bioactivators. Moreover, the use of bioactivator promoted higher averages for soil microbial biomass carbon, soil basal respiration, metabolic quotient, humic acid and humin and reduced the levels of microbial quotient, total organic carbon and fulvic acid.